2015
DOI: 10.34024/rbecotur.2015.v8.6435
|View full text |Cite
|
Sign up to set email alerts
|

Pesca esportiva e pesca artesanal: Lazer e sobrevivência na Hidrelétrica de Tucuruí (PA)

Abstract: Este artigo descreve o cenário que envolve a pesca e suas nuances no lago artificial da hidrelétrica de Tucuruí-Pa (Brasil). Enfatiza as contradições no acesso e uso dos recursos pesqueiros que permeiam realidades bastante antagônicas: um grupo que realiza a pesca esportiva por diversão e lazer e outro de pescadores artesanais que busca o sustento nesta atividade, principal fonte de renda e de alimento. Os procedimentos metodológicos primaram pela investigação junto aos pescadores no interior do lago por meio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The predominance of male fishermen, as observed in our results, in sport fishing events has been a recurrent pattern in this type of fishery around the world (e.g., Argentina (LLompart et al, 2012); France (Herfaut et al, 2013); Canada (Brownscombe et al, 2014); India (Gupta et al, 2016); and USA (ASA, 2016)). In Brazil, other studies have revealed the same pattern: a greater prevalence of male fishermen in sport fisheries, such as in the North (Santos & Oliveira Junior, 1999;Salazar Filho et al, 2005;Silva & Lima, 2015;Souza & Cañete, 2016;Souza et al, 2017), Midwest (Abreu et al, 2015), Southeast (Tsuruda et al, 2013;Peixer & Petrere Júnior, 2009;Tarcitani & Barrella, 2009;Silva et al, 2016) and South (Schork, et al, 2010;Basaglia & Vieira, 2005;Harayashiki et al, 2011;Menezes et al, 2012) regions.…”
Section: Discussionmentioning
confidence: 80%
“…The predominance of male fishermen, as observed in our results, in sport fishing events has been a recurrent pattern in this type of fishery around the world (e.g., Argentina (LLompart et al, 2012); France (Herfaut et al, 2013); Canada (Brownscombe et al, 2014); India (Gupta et al, 2016); and USA (ASA, 2016)). In Brazil, other studies have revealed the same pattern: a greater prevalence of male fishermen in sport fisheries, such as in the North (Santos & Oliveira Junior, 1999;Salazar Filho et al, 2005;Silva & Lima, 2015;Souza & Cañete, 2016;Souza et al, 2017), Midwest (Abreu et al, 2015), Southeast (Tsuruda et al, 2013;Peixer & Petrere Júnior, 2009;Tarcitani & Barrella, 2009;Silva et al, 2016) and South (Schork, et al, 2010;Basaglia & Vieira, 2005;Harayashiki et al, 2011;Menezes et al, 2012) regions.…”
Section: Discussionmentioning
confidence: 80%
“…In a highly impacted environment, sport fishing, perceived hypothetically as an ecotourism activity, imposes a new dynamic on the local artisanal fishers, who are required to provide information on fishing grounds and the geographic features of the reservoir. At the same time, however, the universe of the artisanal fishers has expanded to embrace the wider society through the establishment of market relationships mediated by their knowledge of the local fisheries (Souza and Cañete, 2015).…”
Section: Discussionmentioning
confidence: 99%